MYXEDEMA COMA AS AN EARLY MANIFESTATION OF HASHIMOTO’S THYROIDITIS: A CASE REPORT - Idhayu, Adeputri; Prameswara, Arina; Jayatri, Nindy (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Myxedema coma is a rare, life-threatening endocrine emergency with a high mortality rate that needs early recognition and proper treatment. Most often, this condition can be found in patients with Hashimoto’s thyroiditis or after total thyroidectomy. CASE A 39-year-old female was brought to Emergency Department due to delirium and general weakness. Upon examination, edema, weight gain, dry skin and amenorrhea were also present. There was no history of thyroid disorders. She had hypotension, bradypnea, bradycardia, and was eventually intubated. Laboratory values included TSH 73.17 IU/L, T4 <10.23 nmol/L and anti-TPO 284 IU/mL. A diagnosis of myxedema coma and Hashimoto’s thyroiditis was established, and the patient was treated with levothyroxine and hydrocortisone. Her condition rapidly stabilized. The estimated incidence rate of myxedema coma is 0.22 per million people per year. It is 10 times more common in women. Clinical symptoms include altered mental status, hypothermia, bradycardia, hypotension, and hypoventilation. Physical findings may show a myxedematous facies, which is characterized by generalized puffiness, macroglossia, and a coarse facial appearance. Thyroid hormone measurement clinches the diagnosis. Popovenioic and Chiong also developed a scoring system to help diagnose it. The mortality rate may be as high as 20-60%. Protocols with high doses of thyroid hormone and supportive measures may improve the prognosis. CONCLUSION This case highlights that myxedema coma not only occurs in patients with a prior medical history of thyroid disease but can also be a first manifestation of hypothyroidism.